Flood insurance arrangements in the European Union for future flood risk under climate and socioeconomic change. (September 2019) - Hudson, Paul; Botzen, W.J. Wouter; Aerts, Jeroen C.J.H.
Highlights: Markets need reform to offer financial protection and incentives for risk reduction. Average risk-based flood insurance premium could double between 2015 and 2055. Affordability of flood insurance is improved through Public-Private Partnerships. Support on-going reforms in Europe and abroad that move towards risk-based premiums. Abstract: Flood risk will increase in many areas around the world due to climate change and increase in economic exposure. This implies that adequate flood insurance schemes are needed to adapt to increasing flood risk and to minimise welfare losses for households in flood-prone areas. Flood insurance markets may need reform to offer sufficient and affordable financial protection and incentives for risk reduction. Here, we present the results of a study that aims to evaluate the ability of flood insurance arrangements in Europe to cope with trends in flood risk, using criteria that encompass common elements of the policy debate on flood insurance reform. We show that the average risk-based flood insurance premium could double between 2015 and 2055 in the absence of more risk reduction by households exposed to flooding. We show that part of the expected future increase in flood risk could be limited by flood insurance mechanisms that better incentivise risk reduction by policyholders, which lowers vulnerability. The affordability of flood insurance can be improved by introducing the key features of public-private partnerships (PPPs), which include public reinsurance, limited premium cross-subsidisation between low- and high-risk households, and incentives for policyholder-level risk reduction. These findings were evaluated in a comprehensive sensitivity analysis and support ongoing reforms in Europe and abroad that move towards risk-based premiums and link insurance with risk reduction, strengthen purchase requirements, and engage in multi-stakeholder partnerships.